Effects of antibiotic administration or ZnO replacement strategies on nursery pig performance and a commercial organic acid, essential oil blend on performance of wean-to-finish pigs - Hutchens, Wade Martin (Kansas State University, 2021)
Three experiments were conducted to determine the influence of dietary strategies on nursery pig performance. In Exp. 1, a total of 2,592 pigs were used to determine the effects of two antibiotics (chlortetracycline; CTC vs. tiamulin) and their route of administration (in-feed vs. in-water) on nursery pig growth performance. Although antibiotics did not improve feed efficiency when compared to non-medicated fed pigs, providing CTC in feed with or without tiamulin or tiamulin provided in the water improved nursery pig growth performance. In Exp. 2, 360 weaned pigs were used to evaluate potential replacements for pharmacological levels of Zn (provided by Zn oxide), such as diet acidification (sodium diformate), and dietary crude protein (CP: 21 vs. 18%) on nursery pig performance and fecal dry matter. Although none of the diets had a major influence on fecal dry matter, the addition of pharmacological levels of Zn or sodium diformate independently improved nursery pig performance. In Exp. 3, 1,215 pigs were used to determine the effect of AviPlus, a combination of micro-encapsulated sorbic and citric acids and synthetic thymol and vanillin botanicals, (Vetagro, Inc. Chicago, IL) on growth performance of pigs from weaning to market. When AviPlus was provided during the nursery phase, there was an improvement in G:F in the early and overall nursery phases, but there was no effect on overall wean-to-finish performance.
Keywords: Antibiotic; Zinc; Organic acid; Nursery pigs; Essential oils; Growth performance